Melatonin accelerates reentrainment of the circadian rhythm of its own production after an 8-h advance of the light-dark cycle - Illnerová, H; Trentini, G P; Maslova, L (Journal of comparative physiology. A, Sensory, neural, and behavioral physiology, 1989)
The rhythm in melatonin production in the rat is driven by a circadian rhythm in the pineal N-acetyltransferase (NAT) activity. Rats adapted to an artificial lighting regime of 12 h of light and 12 h of darkness per day were exposed to an 8-h advance of the light-dark regime accomplished by the shortening of one dark period; the effect of melatonin, triazolam and fluoxetine, together with 5-hydroxytryptophan, on the reentrainment of the NAT rhythm was studied. In control rats, the NAT rhythm was abolished during the first 3 cycles following the advance shift. It reappeared during the 4th cycle; however, the phase relationship between the evening rise in activity and the morning decline was still compressed. Melatonin accelerated the NAT rhythm reentrainment. In rats treated chronically with melatonin at the new dark onset, the rhythm had already reappeared during the 3rd cycle, in the middle of the advanced night, and during the 4th cycle, the phase relationship between the evening onset and the morning decline of the NAT activity was the same as before the advance shift. In rats treated chronically with melatonin at the old dark onset or in those treated with melatonin 8 h, 5 h and 2 h after the new dark onset during the 1st, 2nd and 3rd cycle, respectively, following the advance shift, the NAT rhythm reappeared during the 3rd cycle as well but in the last third of the advanced night only. Neither triazolam nor fluoxetine together with 5-hydroxytryptophan administered around the new dark onset facilitated NAT rhythm reentrainment after the 8-h advance of the light-dark cycle.
Keywords: melatonin; Circadian Rhythm; zvířata; epifýza mozková; cirkadiánní rytmus; Acetyltransferases; mužské pohlaví; arylamin-N-acetyltransferasa; Animals; Male; Melatonin; Rats; acetyltransferasy; Rats, Inbred Strains; Pineal Gland; inbrední kmeny potkanů; Arylamine N-Acetyltransferase; krysa rodu Rattus